2015
DOI: 10.1073/pnas.1509262112
|View full text |Cite
|
Sign up to set email alerts
|

Augmenting NMDA receptor signaling boosts experience-dependent neuroplasticity in the adult human brain

Abstract: Experience-dependent plasticity is a fundamental property of the brain. It is critical for everyday function, is impaired in a range of neurological and psychiatric disorders, and frequently depends on long-term potentiation (LTP). Preclinical studies suggest that augmenting N-methyl-D-aspartate receptor (NMDAR) signaling may promote experience-dependent plasticity; however, a lack of noninvasive methods has limited our ability to test this idea in humans until recently. We examined the effects of enhancing NM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 57 publications
3
46
1
Order By: Relevance
“…In contrast to our prior findings of DCS in healthy adults, 50 schizophrenia patients who received DCS performed similarly to patients who received placebo across electrophysiological and learning measures of plasticity. Conversely, among patients who performed above chance, patients who received DCS showed superior 2-back working memory performance compared to patients who received placebo.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast to our prior findings of DCS in healthy adults, 50 schizophrenia patients who received DCS performed similarly to patients who received placebo across electrophysiological and learning measures of plasticity. Conversely, among patients who performed above chance, patients who received DCS showed superior 2-back working memory performance compared to patients who received placebo.…”
Section: Discussioncontrasting
confidence: 99%
“…29,30 Indeed, we previously found that augmenting NMDAR signaling using DCS in healthy adults enhanced VEP potentiation following HFvS and IIT and WPT learning. 50 Controlling for antipsychotic dose, sex, age, and IQ did not alter the similarity of placebo and DCS schizophrenia patients on the plasticity measures, nor did excluding patients who performed around chance for each learning task. Given that the current patients were relatively high-functioning, had low symptom levels, and that the same subgroup of DCS patients showed superior working memory performance over placebo, it is unlikely that confounding factors such as lack of motivation, inattention, or difficulty understanding the tasks accounts for the lack of group differences on plasticity.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In recent years, a few clinical trials have shown efficacy of NMDAR enhancers in schizophrenia, such as DCS, sarcosine, and sodium benzoate. Participants receiving DCS showed enhanced potentiation of neural responses and cognitive performance [64, 65]. Sodium benzoate, as a d-amino acid oxidase inhibitor, significantly improved the PANSS total score and neurocognition in chronic schizophrenia patients [66] (ClinicalTrials.gov NCT00960219.…”
Section: Enhancing Nmdar Functionsmentioning
confidence: 99%